Effects of strengthening exercises on the functional recovery of patients undergoing anterior cruciate ligament reconstruction: An integrative review - Eduardo Melo Rodrigues , Luis; Regia Sales Pontes , Vitória; Vinício Lopes Barros, Marcos; Maria Vieira Mendes , Priscyla; Junior Soares Granja Pereira de Moura , Rogério; Lopes Barros , Francisco; Iago Goncalves Viana Soares Feitosa, Andrei; Lara Ribeiro Dias , Ana; de Sousa Santos , Joselma; de Souza Oliveira, Laire (Seven Editora, 2023)
Introduction: Anterior cruciate ligament (ACL) injury frequently occurs among practitioners of high impact activities and changes in direction, as these individuals have a greater load of tension and develop minor damage to the ligament, which may cause rupture, requiring surgical reconstruction of the ligament. LCA. Decreased strength after reconstruction has been linked to poor function and altered biomechanics, interfering with routine activities of daily living, thus making it impracticable to return to sports activities. Objective: To analyze the effectiveness of strengthening exercises in functional recovery after ACL reconstruction. Methods: The research is an integrative review based on complete articles published in the last 10 years indexed in PubMed and Portal Periódicos CAPES. The following keywords were used to select the articles: “Anterior Cruciate Ligament Reconstruction” AND “Exercise Therapy”; “Anterior Cruciate Ligament Injuries” AND “Exercise Therapy”. Results and discussion: 36 articles were found and 05 selected, where they were unanimous in presenting significantly positive results in the use of exercises in functional rehabilitation after ACL reconstruction. Conclusion: It is concluded that exercise therapy is effective for individuals undergoing ACL reconstruction, the improvement in functionality and the return to the practice of routine or sports activities are directly related to exercise therapy. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-084